Adult friendship - Blieszner, Rosemary M. (Sage series on close relationships., 1992)
A topic relevant to everyone - friendship - is explored in this volume, the first in the SAGE Series on Close Relationships. It presents a thoughtful statement about what we know, and have yet to learn, concerning adults' friendships. The authors discuss state-of-the-art research on the interplay between social structure, individual disposition and dynamic processes of friendship, and findings on both similarities and differences across adult lifecourse stages. They provide a theoretical framework, incorporating both sociological and psychological perspectives.